Análise toxicológica in vitro e in vivo de uma fucana antitrombótica da alga marrom Spatoglossum schdöederi - Lima, Jailma Almeida de (2009)
Fucan is a term used to denominate a family of sulfated polysaccharides rich in L-fucose. They are extracted mainly from the extracellular matrix of brown algae and echinoderms. The brown alga Spatoglossum schröederi (Dictyotaceae) has three heterofucans named A, B and C. Our research group have been extracted non anticoagulant heterofucan from S. schröederi which possess antithrombotic activity in vivo. However, their toxicity in vitro and in vivo has not yet been determined. For the results in toxicity in vitro, we observed that the fucan A at 20, 500 and 1000 μg/plate showed no mutagenic activity in Kado test (Microsuspension), when the bacterial strains TA97a, TA98, TA100 and TA102, with and without S9 were used. The comet assay showed that fucan A (from 20 to 1000 μg/mL) did not cause any genotoxic effect on CHO cells. There was no damage to the DNA of these cells, as evidenced by the tail length and tail moment, which were similar to that found for the negative control. The fucan A from S. schröederi was administered at 20 μg/g of rat (dose which it showed high antithrombotic activity) during two months. After that, the animals were killed and examined. The data showed that fucan A did not cause any change in biochemistry and hematological parameters, as well as, in the morphology and size of the rat s organs analyzed. In conclusion, this study indicates that fucan is a compound with potential pharmacological that has no toxicity